2012
DOI: 10.5296/ijld.v2i3.1817
|View full text |Cite
|
Sign up to set email alerts
|

Role of Islamic Banking in Agriculture Development in Bahawalpur, Pakistan

Abstract: Purpose -The basic purpose of this research paper conducted is to report the findings of this experimental study conducted in Bahawalpur region, about the role of Islamic banking in agriculture sector from the users and non-users (users of conventional banking) of Islamic banking. Design/methodology/approach -This descriptive and qualitative research is conducted and focuses on two main groups of banking customer's users and non users of Islamic banking and also informal interview with managers of some banks. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 8 publications
0
9
0
3
Order By: Relevance
“…Similar studies were conducted in Pakistan by Hassan et al (2012) and Tahir (1996). The former's is titled; Role of Islamic Banking in Agriculture Development in Bahawalpur, Pakistan.…”
Section: Empirical Frameworkmentioning
confidence: 82%
See 1 more Smart Citation
“…Similar studies were conducted in Pakistan by Hassan et al (2012) and Tahir (1996). The former's is titled; Role of Islamic Banking in Agriculture Development in Bahawalpur, Pakistan.…”
Section: Empirical Frameworkmentioning
confidence: 82%
“…Muzara'ah Agricultural Financing Scale (MAFS) was the structured questionnaire used for collecting primary data from the target respondents in Kura Local government area from the total sample size of 250 farmers. Furthermore, Chi square test of goodness of fit was adopted for data analysis and justified in line with the previous researchers, such as Hassan et al (2012).…”
Section: Methodsmentioning
confidence: 94%
“…Murabahah finance is an Islamic financial product used in the purchase of goods and sells it to the client on agreed price and profit margin (5). Also, Hassan et al (13) refer Murabahah finance as a mutually stipulated margin of profit in a sale transaction, where the cost of the commodity is known or made known to the buyer. The parties negotiate the profit margin on cost and not the cost per se.…”
Section: Literature Review On Murabahah Financementioning
confidence: 99%
“…In addition, it is empirically revealed that Murabahah financing is the most popular credit sales or deferred sale in relations to empowering both farmers and traders in accordance to the Qur'anic legitimacy (1, 3, 15-18). More so, (8,13) stated that, Murabahah financing has two different modes of payment: either paying the total amount at the time of the sale in cash or paying on credit. Additionally, clients can pay on credit, also known as bay' al-muajjil in Arabic, in two ways: payment of the lump sum at some point in the future or payments in instalments.…”
Section: Literature Review On Murabahah Financementioning
confidence: 99%
See 1 more Smart Citation